Interpreting Meaning in Social Criticism through Murals in Indonesia - Parani, Rizaldi; Darmawan, Samuel Aditya; Purba, Herman (Nyimak: Journal of Communication, 2023)
Murals, as a form of street art, are increasingly used not only to enhance urban aesthetics but also to convey social criticism. In Indonesia, this trend has gained momentum, particularly during the Covid-19 pandemic, when murals have become a medium for dissent against government policies, figures, and institutions. This study aims to analyze how artists use murals to express social criticism towards the government and to understand the interpretative process involved in their message delivery. Utilizing Social Construction theory, this research examines how artists construct and convey their messages through murals. The study adopts a qualitative approach with a phenomenological method, focusing on the lived experiences of the artists to gain insights into how they perceive and represent social realities. The findings reveal that mural creation is a subjective process, deeply influenced by the artists' understanding of social issues. Artists navigate through various stages of construction, incorporating words, symbols, and images to reflect their perspectives on societal concerns. The messages embedded in these murals are often open to multiple interpretations, reflecting the diverse ways in which social criticism can be communicated. This study highlights the role of murals as a dynamic form of protest and expression, revealing the complex interplay between artistic representation and social critique. The research underscores the importance of considering artists' experiences and perspectives to fully appreciate the impact and significance of their work in the context of social and political commentary.Keywords: Social construction, meaning, interpretation, mural, social criticism ABSTRAKMural, sebagai bentuk seni jalanan, semakin digunakan tidak hanya untuk meningkatkan estetika perkotaan tetapi juga untuk menyampaikan kritik sosial. Di Indonesia, tren ini semakin berkembang, terutama selama pandemi Covid-19, ketika mural menjadi media untuk mengekspresikan ketidakpuasan terhadap kebijakan pemerintah, tokoh, dan institusi. Penelitian ini bertujuan untuk menganalisis bagaimana seniman menggunakan mural untuk menyampaikan kritik sosial terhadap pemerintah dan untuk memahami proses interpretasi yang terlibat dalam penyampaian pesan mereka. Menggunakan teori Konstruksi Sosial, penelitian ini memeriksa bagaimana seniman membangun dan menyampaikan pesan mereka melalui mural. Studi ini mengadopsi pendekatan kualitatif dengan metode fenomenologis, berfokus pada pengalaman hidup para seniman untuk mendapatkan wawasan tentang bagaimana mereka memandang dan merepresentasikan realitas sosial. Temuan penelitian menunjukkan bahwa penciptaan mural adalah proses subjektif, yang sangat dipengaruhi oleh pemahaman seniman terhadap isu-isu sosial. Seniman melewati berbagai tahap konstruksi, menggabungkan kata-kata, simbol, dan gambar untuk mencerminkan perspektif mereka tentang masalah-masalah masyarakat. Pesan yang tertanam dalam mural ini sering kali terbuka untuk berbagai interpretasi, mencerminkan cara-cara beragam dalam menyampaikan kritik sosial. Penelitian ini menyoroti peran mural sebagai bentuk protes dan ekspresi yang dinamis, mengungkapkan hubungan kompleks antara representasi artistik dan kritik sosial. Penelitian ini menekankan pentingnya mempertimbangkan pengalaman dan perspektif seniman untuk sepenuhnya menghargai dampak dan signifikansi karya mereka dalam konteks komentar sosial dan politik.Kata Kunci: Konstruksi sosial, makna, interpretasi, mural, kritik sosial